2014
DOI: 10.1016/j.neurobiolaging.2014.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E and lipid homeostasis in the etiology and treatment of sporadic Alzheimer's disease

Abstract: The discovery that the apolipoprotein E (apoE) ε4 allele is genetically linked to both sporadic and familial late-onset Alzheimer's disease (AD) raises the possibility that a dysfunction of the lipid transport system could seriously affect lipid homeostasis in the brain of AD subjects. The presence of the ε4 allele has been associated with lower levels of apoE in both serum and brain tissues of normal and AD subjects. In an attempt to reverse the apoE deficit in AD, we identified and characterized several apoE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 74 publications
2
69
0
Order By: Relevance
“…Identification of potentially modifiable risk factors for Alzheimer's disease can help us develop some effective interventions to reduce risk of Alzheimer's disease [43,44]. In addition, for individuals with high risk of Alzheimer's disease, early interventions may be necessary [45].…”
Section: Discussionmentioning
confidence: 99%
“…Identification of potentially modifiable risk factors for Alzheimer's disease can help us develop some effective interventions to reduce risk of Alzheimer's disease [43,44]. In addition, for individuals with high risk of Alzheimer's disease, early interventions may be necessary [45].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that APOE4 can result in excessive amyloid build up, interference with Tau metabolism, and/or disrupt lipid homeostasis and reduced neuronal plasticity; upregulating APOE levels might thus be protective. There is thus a close relationship between cholesterol transport and amyloid deposition-although the precise interrelationship needs to be clarified [244,245]. Although an interesting effect, the possible influence of CBD on cholesterol efflux has not been further verified, and the precise molecular targets are not known; the concentrations required are also quite high.…”
Section: Cbd Transporter Targets In Neurodegenerationmentioning
confidence: 99%
“…Specifically, NMEs that target acetylcholinesterase (AChE) 18 or N-methyl-D-aspartate (NMDA) receptors 19 were discovered through research on these neurotransmitter pathways and were only later applied to AD therapy. Moreover, the most common genetic risk factor for both sporadic and familial forms of AD, the apolipoprotein E4 allele, 20 was first described as a risk factor for cardiovascular disease and is now considered an important biomarker in AD. In fact, 1 of the important strategies for current research is repurposing drugs from other indications.…”
Section: Introductionmentioning
confidence: 99%